Comprehensive review of LCA studies in Civil Engineering - Thapa, Ishwor; Baral, Nirmal Prasad; Adhikari, Krishna Raj (BIBECHANA, 2023)
This review paper explores the application of Life Cycle Assessment (LCA) within the domain of civil engineering, aiming to provide a comprehensive overview of current research, methodologies, challenges, and future trends. LCA serves as a pivotal tool for assessing the environmental impact of infrastructure projects, yet gaps persist in its integration with socioeconomic dimensions, regional considerations, and dynamic modeling. By analyzing existing literature and scholarly discussions, this review identifies research gaps and proposes directions for enhancing the applicability and effectiveness of LCA in civil engineering. Moreover, it examines future trends such as the integration of advanced technologies, stakeholder engagement, and policy implementation, poised to shape the landscape of LCA practices in the civil engineering sector. Ultimately, this review paper contributes to the understanding of LCA's potential to drive sustainable decision-making in infrastructure development, paving the way for more informed and environmentally conscious practices.